Analisis Swot Terhadap Strategi Pemasaran Syariah Pada WM Boutique Di Kabupaten Gowa - Lisa Indrywati; Idris Parakkasi; A. Syathir Sofyan (LPPM, 2022)
Business cannot exist without competition, definitely plays an important role in any marketing campaign. No single business can be the sole winner in terms of sales and profits; instead, other businesses will compete for that success. As a result, this leads to a focus on competition in any marketing effort. The aims of this study were (1) to find out the form of the sharia marketing strategy carried out by WM boutique (2) to find out the SWOT analysis of the implementation of the sharia marketing strategy at WM Boutique. This type of research uses qualitative and quantitative methods to obtain information. qualitative and quantitative information leads to better research results. This method allows researchers to use several research methods and collect data through inductive and deductive thinking. Collecting multiple data points also solves research problems using different data sources. Research results (1) WM's business continues to improve the quality of its products. Doing so proved impossible to ignore when competing with other industries for customers. In addition, promoting product location and availability helps attract new customers. Because the location is a strategic place, people automatically want to buy goods there. When looking at promotional strategies for online marketing promotions, the focus lies on WM Boutique's promotional strategies. (2) Through SWOT analysis, it is known that WM boutique currently has internal strengths as well as many external opportunities so that in order to continue to exist, WM boutique must be able to take advantage of opportunities and develop its strengths.